Mangrove Degradation: Reversing the Trend through Community Engagement - Wang'ondu, Virginia (University of Nairobi, 2020)
More than 3,000 fish species, crabs, shrimps, prawns, molluscs, and oysters, among others, live, shelter and breed in the mangrove forests. Marine fishing is an important economic activity and a major income earner, producing 8,000 tons of marine fish, generating KES 100 million annually, and contributing approximately 0.5 per cent of all the goods and services produced in the country. Marine fish is also an important protein source for inland and coastal communities. Destruction and clearance of mangrove forests through logging and over-harvesting directly affects inshore and offshore commercial fisheries through lack of food and loss of shelter and breeding grounds for most fish, threatening their survival. Also, the decline in fish numbers causes a loss of vital income and a much-needed protein source, resulting in malnutrition and food insecurity. In Kenya, the losses are estimated at KES 582 million every year for inshore fisheries within the mangroves.
Keywords: Kenya; Environment